Behavioural economics, libertarian paternalism and freedom to choose - Rodriguez Cairo, Vladimir (2018)
The article explains the fundamentals of the Behavioral Economics also known as Economic Psychology or simply Psychology and Economics. It is the one that through experimental and observational designs seeks to detect errors that are made in making decisions. It is in this sense, that Behavioral Economy uses the concepts and evidence of psychology to improve the understanding of the economic decision-making process, analyzing the reasons why people generally make inappropriate decisions. It is from this perspective that Richard Thaler and Cass Sunstein formulate Libertarian Paternalism with the purpose of designing public policies to maintain or increase people's freedom of choice as to improve the conditions or contexts for making appropriate decisions.